Asymmetric and heterogeneous impacts of climate policy uncertainty on risk spillovers in China’s traditional energy sector: A tail risk spillover network approach - Jing Deng; Susa Wang; Haoyi Hou; Jianing Zheng; Shuqi Yin; Guorong Chen (Sustainable Futures)
This study employs the tail-event-driven-network model to construct a dynamic network and explores nonlinear tail risk spillover effects within subindustries and across corporations in China’s traditional energy sector from both dynamic and static perspectives. It introduces China’s climate policy uncertainty and applies the quantile-on-quantile regression model to evaluate the heterogeneous impacts. The findings indicate that: (1) risk spillovers in traditional energy markets intensify during major event shocks; (2) the coal industry emerges as the primary emitter and recipient of tail risk spillovers; and (3) climate policy uncertainty has heterogeneous effects on risk spillovers, with sensitivities varying across industries.